Necessity of Innovative Development of Tourism - Z.Muhammedova (Indonesian Journal of Innovation Studies, 2019)
One of the features of the modern world economy is that tourism is one of the fastest-growing and highly profitable sectors of the economy. Accordingly, the article presents the work of many scholars and researchers on the need for innovative tourism development. At the same time, there were suggestions and proposals on the measures taken on the need for innovative tourism development.